ANALISIS STRATEGIK IMPLEMENTASI MANAJEMEN PENINGKATAN MUTU BERBASIS SEKOLAH (MPMBS) (STUDI KASUS: SMP NEGERI 23 KOTA BANDUNG) - ., ARDITARYANTO; AGUSTIANA S, RIMA (Politeknik Dharma Patria Kebumen, 2017)
Purpose  ?  To  know  the  implementation  of  school-based  quality  improvement  management (MPMBS) in an effort to improve the effectiveness of learning process at SMP Negeri 23 Bandung. Findings ? The declining quality and competitiveness of education have become one of the obstacles in preparing the reliable human resources and the spirit of global level competition, so that the right strategy is needed to overcome them. Methodology ?The steps taken in the research is using Qualitative Descriptive approach method. Technique of collecting data was done by observation, interview by circulating questionnaire, and documentation study. Data analysis model used is strategy formulation through data reduction, conclusion, verification and SWOT analysis calculation. Testing and Realization ? The result of calculation usingthe Cartesian SWOT diagram is that the coordinate point of school position is at power axis point 0.60 and axis probability 0.75 for strength (S) = 1.80, weakness (W) = 1.20, opportunity (O) = 1.95 and threat (T) = 1.20. The internal Factor Analysis shows a power figure of 1.80 on a scale of 1 to 4 indicates a number that is still lacking in the power category. The difference between S and W is relatively small (0.60), means that the strength is possible to cover the weakness if the school do things that contribute to the power aspect. The External Factor Analysis shows the number of opportunities (O) = 1.95 and Threat (T) = 1.20. The difference between O and T is 0.75 can be used as an input to improve the ability and look for other opportunities from outside. In the analysis of Cartesian SWOT diagram with strength axispoint 0.60 and probability axis0.75 can be obtained a strategy that is considered appropriate for the school,  that  is  the  aggressive  strategy,  to  improve  the  power  aspects  (S)  to  obtain  value Opportunities (O) from the outside effectively and efficiently